2012
DOI: 10.4314/ijbcs.v6i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of flour and bread from sweet potato wheat composite flour blends

Abstract: This study was to assess the quality of the flour and bread produced from sweet potato wheat composite flour blends. Matured and freshly harvested sweet potato (Ipomea batatas L.) was obtained from a local market in Akure, Nigeria. The tubers were thoroughly washed, peeled, washed again, drained, chipped, oven dried, milled, sieved and packaged. Five blends were prepared by homogenously mixing sweet potato flour with wheat flour in the percentage proportions of: 0:100, 5:95, 10:90, 15:85 and 100:0 (PF: WF) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 8 publications
2
23
1
1
Order By: Relevance
“…; Oluwalana et al. ;. Loaf volume and specific volume decrease might be due to decrease in gluten network in dough and less ability of the dough to rise, due to weaker cell structure (Chavan and Kadam ; Abdelghafor et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…; Oluwalana et al. ;. Loaf volume and specific volume decrease might be due to decrease in gluten network in dough and less ability of the dough to rise, due to weaker cell structure (Chavan and Kadam ; Abdelghafor et al.…”
Section: Resultsmentioning
confidence: 99%
“…Increase in percentage of GHF decreased the loaf volume and specific volume of bread, but increased the loaf weight (Table 4). Specific loaf volume was found to be greater than that of composite bread prepared by Dooshima et al (2014); Ndife et al (2011) and less compared to findings of Onuegbu et al 2013;Oluwalana et al 2012;. Loaf volume and specific volume decrease might be due to decrease in gluten network in dough and less ability of the dough to rise, due to weaker cell structure (Chavan and Kadam 1993;Abdelghafor et al 2011).…”
Section: Physical Characteristics Of Bread Prepared From Different Comentioning
confidence: 91%
See 1 more Smart Citation
“…This is less than the range of 10.15% -12.44% obtained by Oluwalana et al (2012) for sweet potato-wheat bread. This difference may be due to inclusion of tiger nut in the composite flour.…”
Section: Resultsmentioning
confidence: 58%
“…Despite this it is yet to be fully exploited (Woolfe, 1992), and is still perceived as an underutilized yet nutritious food (Woolfe, 1992;Bovell-Benjamin, 2007;Rodriguez-Amaya et al, 2011). Oluwalana et al, 2012 reported that wheat flour could be substituted with as much as 15% sweet potato flour in bread making without adversely affecting the physicochemical and sensory properties. Micronutrient deficiency also known as hidden hunger is one of the major problems faced by developing countries such as Nigeria usually in relation to health and nutrition of its young children.…”
Section: Introductionmentioning
confidence: 99%